Variabilidade fenotípica e potencial de enraizamento por estaquia de genótipos de erva-mate cambona 4 - Hettwer, Valesca Franciele Joana Mello (2013)
The seedling production of mate by seeds is a factor of genetic variability and difficulty to establish a standard of productivity and quality of raw material, and the cutting propagation is an alternative to deploying uniform herbal. The objective of this study was to evaluate the phenotypic variability of a Cambona 4 commercial herbal, implanted with seedlings obtained from seeds and the variation in the potential for rooting cuttings. Two experiments were conducted. At first it was studied the phenotypic variability of 14 plants (genotypes) selected among different characteristics of branches and leaves in a herbal located in Machadinho, in the state of Rio Grande do Sul - Brazil. In the second experiment, it was checked the possible variability in rooting potential of cuttings of selected genotypes, carrying the cuttings from January to early April, with and without application of 6000 mg L-1 indolebutyric acid (IBA). The results demonstrated that the production of seedlings of Cambona 4 by seeds, while restricting the crossing between a male and another female selected, generates phenotypic variability, not being high the prevalence of the characteristics of either parent plants from the crossing. Leaf area and the number of leaves per meter were the most determinant variables of divergence between genotypes. In the cutting was found that the percentage of survival, leaf retention and rooting varied between genotypes and the survival and retention of leaves was satisfactory, especially in the first month of cutting, which is considered the most critical moment. The using of IBA stimulated, or at least not damaged the rooting, but depending on the genotype, it reduced survival and in a greater extent the leaf retention. Using the IBA, the rooting ranged between 2.1% and 52.6% but higher rates obtained by performing the process again with the stakes that have been kept alive seem to indicate the need to extend the period beyond 90 cuttings days. Thus, given the phenotypic variability and rooting observed, it can be said that the production of seedlings by cutting necessarily involves the selection of matrices that can represent the standard of Cambona 4 and hold high potential for rooting